Synthesis of (E)‐1‐(phenyldiazenyl)cyclohexyl Benzoate from N‐(cyclohexylideneamino)aniline and Benzoyl Peroxide. Issue 27 (20th July 2022) - Zhu, Wenjing; Chen, Yu; Yu, Xiao; Liu, Hongyan; Zhang, Zheng; Wen, Fuqiang; Liu, Yi; Zhang, Pengfei; Xia, Chengcai; Li, Furong
Abstract: A method of synthesis ( E )‐1‐(phenyldiazenyl)cyclohexyl benzoate from N ‐(cyclohexylideneamino)aniline has been developed. The reaction could proceed smoothly under N2 atmosphere at 80 °C in CH2 Cl2 and 22 examples of products were obtained. Abstract : Herein, we report a method for the synthesis of ( E )‐1‐(phenyldiazenyl)cyclohexyl benzoate, which can synthesize azo compounds in high yield by arylhydrazine oxidation. The reaction is characterized by mild conditions, metal‐free catalysis and high yield, which provides a new idea for the synthesis of azo compounds.